Oral administration of vitamin C decreases muscle mitochondrial biogenesis and hampers training-induced adaptations in endurance performance - Gomez-Cabrera, M.-C.; Domenech, E.; Romagnoli, M.; Arduini, A.; Borras, C.; Pallardo, F. V.; Sastre, J.; Vina, J. (The American Journal of Clinical Nutrition, 2008)
Exercise practitioners often take vitamin C supplements because intense muscular contractile activity can result in oxidative stress, as indicated by altered muscle and blood glutathione concentrations and increases in protein, DNA, and lipid peroxidation. There is, however, considerable debate regarding the beneficial health effects of vitamin C supplementation.